THBS4 silencing regulates the cancer stem cell‐like properties in prostate cancer via blocking the PI3K/Akt pathway. Issue 10 (18th May 2020) - Hou, Yi; Li, Hai; Huo, Wei
Abstract: Background: Although thrombospondins 4 (THBS4) participates in controlling the biology of prostate cancer (PCa), the mechanism underlying this regulation remains unknown. Hence, this study aims to identify the regulatory effects of THBS4 on the PCa stem cell‐like properties and the potential mechanism associated with the phosphatidylinositol 3′‐kinase (PI3K)/protein kinase B (Akt) pathway. Methods: PCa stem cells were sorted and identified using flow cytometry and THBS4 expression in the identified PCa stem cells was measured using Western blot assay. THBS4 was overexpressed or silenced in PCa stem cells, following which, self‐renewal, proliferation, cell cycle distribution, and apoptosis of PCa stem cells were assessed as well as tumorigenicity in vivo was evaluated. PI3K/Akt pathway inhibitor was applied to identify its involvement in the regulatory roles of THBS4 in PCa stem cells. Results: THBS4 was expressed at a higher level in PCa stem cells than in PCa cells. The overexpression of THBS4 promoted the self‐renewal and proliferation, curbed the apoptosis of PCa stem cells, and enhanced the in vivo tumorigenicity, which was achieved by activating the PI3K/Akt pathway. On the contrary, short‐hairpin RNA‐mediated silencing of THBS4 exhibited suppressive effects on those cancer stem cell (CSC)‐like properties and promotive effects on their apoptosis. Conclusion: THBS4 silencing can impede the CSC‐like properties in PCa via blockade of the PI3K/Akt pathway, which provides patients with PCa a new therapeutic target.